Enteric Type Bartholin Gland Adenocarcinoma: An Unusual Variant of a Rare Neoplasm. (23rd March 2021) - Robinson, Harry; Karpe, Manali; Edidi, Ibrahim; Fisher, Ann; Drew, Yvette; Ralte, Angela; O'Donnell, Rachel L.
Abstract : Vulval cancer is rare. With Bartholin gland carcinomas representing <5% of all vulval carcinomas they present both diagnostic and management challenges. There are a small number of cases in the literature describing Bartholin gland carcinomas with unusual histology which necessitates the need to explore the possibility of metastases from elsewhere. We present a case of a 55-yr-old woman presenting with a vulval lesion within the Bartholin gland. Morphology demonstrated enteric type adenocarcinoma and the immunohistochemistry profile was positive for CK7, CK20, CDX2, CEA, and CA19-9. There was no evidence of an alternative primary cancer and the tumor was excised with negative regional sentinel node assessment. Genotyping showed no detectable mutations in KRAS, BRAF or NRAS suggesting a possible future role for anti-EGFR therapy.